2022
DOI: 10.1016/j.jvs.2021.11.066
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictive factors for endograft limb patency of the fenestrated Anaconda endograft used for complex endovascular aneurysm repair

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Furthermore, Stehr et al 39 reported a substantial reduction of the median aneurysm diameter from 56.7 to 49.0 mm after 6 months ( P = 0.05). Lastly, de Niet et al 43 (335 patients) found that 97.9 ± 0.9% of patients were free from AAA growth. The above evidence proves that the Anaconda™ SG promotes excellent sac regression thereby significantly decreasing AAA diameter.…”
Section: The Terumo Aortic Anaconda™ Sgmentioning
confidence: 97%
“…Furthermore, Stehr et al 39 reported a substantial reduction of the median aneurysm diameter from 56.7 to 49.0 mm after 6 months ( P = 0.05). Lastly, de Niet et al 43 (335 patients) found that 97.9 ± 0.9% of patients were free from AAA growth. The above evidence proves that the Anaconda™ SG promotes excellent sac regression thereby significantly decreasing AAA diameter.…”
Section: The Terumo Aortic Anaconda™ Sgmentioning
confidence: 97%